2004
DOI: 10.1080/08958370490476749
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Histopathological Change Determined by the Point Counting Method and Its Application for the Hazard Assessment of Respirable Dust

Abstract: We evaluate the morphometric point counting method (PCM) for qualitatively analyzing pulmonary inflammation and collagen deposits (i.e., fibrosis) in the assessment of the biological hazards of inhaled respirable particles at a realistic dose comparable to that of exposure in the work environment. Rats were exposed by intratracheal instillation to a 2-mg dose, which is close to the estimated overdose at which macrophage clearance is impared, of each of 3 kinds of particulate matter: crystalline silica, crocido… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 19 publications
1
15
0
Order By: Relevance
“…Potter et al 11) reported that lung burden increased progressively in rat lungs exposed to crystalline silica (15 mg/m 3 , 6 h/d, 5 d/wk) from the start of exposure and that a lung burden of 2 mg of silica was equivalent to the dose of silica that would result from approximately 30 d of inhalation. In this experiment, granulomatous formations including silica were not observed 12) . The expression of EC-SOD was increased not only at the mRNA level but also at the protein level.…”
Section: Discussionmentioning
confidence: 81%
“…Potter et al 11) reported that lung burden increased progressively in rat lungs exposed to crystalline silica (15 mg/m 3 , 6 h/d, 5 d/wk) from the start of exposure and that a lung burden of 2 mg of silica was equivalent to the dose of silica that would result from approximately 30 d of inhalation. In this experiment, granulomatous formations including silica were not observed 12) . The expression of EC-SOD was increased not only at the mRNA level but also at the protein level.…”
Section: Discussionmentioning
confidence: 81%
“…Sections were stained with hematoxylin-eosin (HE). The procedure for evaluation of inflammatory areas has been described elsewhere 14) . Six images per HE-stained section were digitally captured at random.…”
Section: Morphological Procedures Of Pulmonary Tissuementioning
confidence: 99%
“…Histopathological changes of the lung after exposure to PT1 and CS, which show high biopersistence in the lung, were observed in our previous experiment. For CS, expanding alveolitis, type II epitheliall-cell hypertrophy and hyperplasia, and alveolar lipoproteinosis were observed 15) , and for PT1, mild fibrotic changes around macrophages that had engulfed the fibers were observed 16) . Based on these results and the results of the present study, we consider that highly soluble particles and fibers are rapidly cleared from the lung while having only minor effects on the lung.…”
Section: Resultsmentioning
confidence: 99%